What fills your cup of coffee? The potential of geographical indication for family farmers' market access - Lourenzani, Ana Elisa Bressan Smith [UNESP]; Watanabe, Kassia; Pigatto, Giuliana Aparecida Santini [UNESP]; de Godoi Pereira, Mara Elena [UNESP] (Elsevier, 2019)
Coffee is one of the most consumed food products in the world. In general, it is produced by family farmers in the tropics, often at risk of poverty conditions and in close interaction with highly biodiverse biomes. The characteristics of family farming make this category more susceptible to market distortions. For family farming, the adoption of geographic indication (GI) can be a strategy for strengthening activity, access to markets, and adding value to agricultural and nonagricultural activity, such as tourism and gastronomy. This chapter aims at analyzing GI as a strategy to facilitate market access for family farmers. Based on some evidences from Brazil, GI has high potential to fill your cup of coffee with quality and intangible values as tradition, culture, social value, and local development incentive. To do so, multiactor governance must be designed.
Keywords: Coffee; Family farming; Geographical indication